Is Project-Based Learning a Guaranteed Boost for Students' Creativity? A Meta-Analytic Review - Hera Puspita Sari; Arys Rafiah; Ilham Falani (Jurnal Penelitian Pendidikan IPA, 2025)
This study aimed to conduct a meta-analysis to examine the impact of Project-Based Learning (PjBL) on the development of creative thinking skills among junior high school students in science learning. A meta-analysis method was employed by collecting and analyzing 10 relevant articles published between 2019 and 2024 from national journals indexed at least Sinta 4 and international journals or proceedings. The results indicated that PjBL significantly improved junior high school students' creative thinking skills in science learning. The effect size obtained showed a strong influence of PBL on students' creative thinking skills. Based on the grade level, the effect size for grade 7 was 0.94, for grade 8 was 4.76, and for grade 9 was 1.06, all of which were categorized as high. The success of project-based learning hinges on the appropriate selection of materials, consideration of individual student needs, and effective teacher guidance. Each student possesses unique learning styles and abilities, necessitating individualized project assignments. Time management skills are crucial for students to achieve their learning goals and produce high-quality work. The findings of this study have important implications for the development of science curricula and teaching practices at the junior high school level, and suggest the need for further research to investigate factors that can maximize the effectiveness of PjBL in developing students' creative thinking skills.